Green synthesis of hyaluronic acid coated, thiolated chitosan nanoparticles for CD44 targeted delivery and sustained release of Cisplatin in cervical carcinoma - Kousar, Kousain; Naseer, Faiza; Abduh, Maisa S.; Kakar, Salik; Gul, Rabia; Anjum, Sadia; Ahmad, Tahir (Frontiers in Pharmacology, 2023)
Cervical carcinoma is one of the most prevalent gynecological cancers throughout the world. Cisplatin is used as first line chemotherapy for treatment of cervical cancer, but it comes with plethora of side effects. The aim of this study was to develop hyaluronic acid coated, thiolated chitosan nanocarriers using green synthesis approach, for CD44 targeted delivery and sustained release of Cisplatin in cervical cancer cells. After synthesis through ionic gelation method, Zeta analysis showed that the nanoparticle size was 265.9 nm with a zeta potential of +22.3 mV and 0.226 PDI. SEM and TEM analysis confirmed the spherical shape and smooth surface of nanoparticles. FTIR and XRD showed the presence of characteristic functional groups, successful encapsulation of drug, and crystalline nature of nanoparticles respectively. Drug loading and entrapment efficiency were calculated to be 70.1 ± 1.2% and 45 ± 0.28% respectively. Analysis of in vitro drug release kinetics showed that drug release followed the Higuchi model at pH 6.8 and 7.4 and Cisplatin release for up to 72 hours confirmed sustained release. In vitro analysis on cervical cancer cells HeLa and normal cervical epithelial cells HCK1T was done through cell morphology analysis, trypan blue assay (concentration range of 10-80µg/mL), and MTT cytotoxic assay (concentration range of 10-90µg/ mL ).The results showed a higher cytotoxic potential of HA coated, thiolated chitosan encapsulated Cisplatin (HA-ThCs-Cis NP) nanoformulation as compared to pure Cisplatin in HeLa while in HCK1T, pure Cisplatin showed much higher toxicity as compared to HA-ThCs-Cis nanoformulation. These findings suggest that CD44 targeted delivery system can be a useful approach to minimize offtarget toxicities, give sustained release and better cellular uptake in cancer cells.